Evaluation of Some Maize Genotype’s Performance and Their Susceptibility to Corn Stem Borer Under the Effect of Potassium Spraying - Omar Karim Hassoun; Raeed Mejbel Abdullah; Karim Abdullah Hassan (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2025)
This study took a close look at different types of corn plants (Zea mays L.) to see how well they stood up against the corn stem borer, Sesamia cretica. We also explored how applying potassium to the leaves affected their resistance. The experiment happened during the summer growing season of 2024 at the University of Kirkuk's Agricultural Research and Experiment Station. We used a standard experimental setup, repeating our tests three times. We tried three different potassium concentrations (0, 15, and 30 grams per liter) and tested six distinct corn varieties: KONSENS, DKC777, DKC666, AGN720, GAMESON, and GOLDEN. We measured several things: how much the plants got infected, the number of holes, larvae, and tunnels in each plant, and how much of the stem was eaten away. Our statistical analysis showed that both the potassium application and the type of corn plant, as well as their combination, had a big impact on most of the traits we measured. The only exceptions were the infection rate, the number of larvae, and the excavated distance when considering the interaction between the plant type and potassium. Interestingly, the 'GAMESON' corn variety consistently showed the best resistance. It had the lowest infection rate (15.94%), the fewest holes (5.31), larvae (1.51), tunnels (2.18), and the least stem damage (17.36%). Applying potassium at 30 grams per liter also significantly helped, reducing the infection rate to 16.38%, holes to 2.73, tunnels to 2.52, and stem damage to 16.80%. The best results came from combining the 'GAMESON' variety with the 30 gm/L potassium treatment, leading to the absolute minimum number of holes (1.86) and tunnels (1.46). This really highlights how much this combination boosts resistance. Our findings strongly suggest that using resistant corn varieties like 'GAMESON' along with smart potassium fertilization can significantly protect corn crops from the stem borer.